Exercise and COVID‐19: reasons individuals sought coaching support to assist them to increase physical activity during COVID‐19 - Stephen Barrett; Kane Rodda; Stephen Begg; Paul D. O'Halloran; Michael I. Kingsley (Australian and New Zealand Journal of Public Health, 2021)
Abstract Objective: This paper explores the experiences of individuals who reported substantially decreasing physical activity (PA) as a result of COVID‐19 and sought coaching support to increase PA. Methods: A qualitative study using phenomenological analysis. Eight individuals participated in semi‐structured interviews that focused on their experiences of decreasing PA as a result of physical distancing measures, and why they sought PA coaching to overcome these issues. Responses were analysed thematically. Results: The participants reported markedly decreasing their PA following the enactment of physical distancing measures. The inability to subsequently engage in regular PA was a source of frustration for participants. Interview analysis revealed two themes that contributed to the understanding of why these individuals felt they needed PA coaching to increase PA; namely, a desire for both listening support and PA self‐regulation support. Conclusion: The individuals who decreased PA due to COVID‐19 desired an autonomy‐supportive counselling style, centred on listening support and self‐regulatory support. Online PA interventions were not highlighted as strategies to overcome PA barriers. Implications for public health: The effect of physical distancing measures on the determinants of overall PA is important, particularly if prolonged physical distancing is required.